THE EVALUATION OF SOIL EROSION OFF-SITES EFFECTS IN LARGE BASINS: THE STUDYCASE OF LERMA-CHAPALA WATERSHED, MEXICO - Helena Cotler A.; Susana Gutierrez D.; Carlos Enriquez G.; Arturo Garrido P. (Sociedade & Natureza)
One of the primary global concerns during the new millennium is the assessment of the impact of accelerated soil erosion on the economy and the environment (Pimentel et al. 1995; Lal, 1995). Erosion damages the site on which it occurs and also has undesirable effects off-site in the larger environment. Erosion moves sediments and nutrients out of the land, creating the two most widespread water pollution problems in the rivers, lakes and dams. The nutrients impact water quality largely through the process of eutrophication caused by an excessive content of nitrogen and phosphorus. In addition to the nutrients presence, sediment and runoff may also carry toxic metals and organic compounds, such as pesticides (Brady and Weil, 1999; Lal, 1994; de Graaf, 2000; Renschler and Harbor, 2002). The sediment itself is a major pollutant causative agent, causing a wide range of environmental damages. The sedimentation of dams and canals, reduces their lifetime and efficiency, promoting a high restoration cost to the downstream users and affecting thenational budget. In this sense, sedimentation knowledge is an important tool to guide spatial planning efficiently. Despite more than six decades of research, sedimentation is still probably the most serious technical problem faced by the dam industry (Mc Cully, 2001). Many studies estimate present-day fluvial sediment and solute loads including both natural and accelerated soil erosion (Douglas, 1990). However, as Douglas mentioned (op.cit) many do not include all the erosion caused by human activity, because the eroded sediment is redeposited after a short movement downslope. Many soil particles are detached and carried downslope only to be held and trapped by a plant, tree or other obstacle a little further downslope. The sediment reaching the valley floor may not be completely removed by the river, but may be redistributed as alluvial floodplain deposits. The sediment transported downstream may be redeposited again on another part of the floodplain or in managed rivers in reservoirs.